Effects of Sleep Quality, Acute Sleep Deprivation, and Napping on Facial Emotion Recognition Accuracy and Speed - Huang Y; Li Y; Su T; Wang H; Xu S; Xu J; Zheng S; Du J; Wang Y; Zhang R; Meng Y; Guo X; et al. (Nature and Science of Sleep)
Yujia Huang,1,2,* Yinan Li,2,* Tong Su,3 Hao Wang,2 Shuyu Xu,2 Jingzhou Xu,2 Siqi Zheng,4 Jing Du,2 Yajing Wang,2 Ruike Zhang,2 Yao Meng,2 Xin Guo,2 Lei Xiao,2 Yunxiang Tang3 1Psychology Department, The Second Naval Hospital of Southern Theater Command, Sanya, People’s Republic of China; 2Department of Medical Psychology, Faculty of Psychology, Naval Medical University, Shanghai, People’s Republic of China; 3Faculty of Psychology, Naval Medical University, Shanghai, People’s Republic of China; 4Department of Psychology, TongJi University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Xiao; Yunxiang Tang, Email xiaolei0237@163.com; tangyun7633@sina.comObjective: To investigate the effects of sleep quality, sleep deprivation, and napping on facial emotion recognition (FER) accuracy and speed.Methods: This research included a cross-sectional study (102 qualified participants) and a randomized controlled study (26 in the napping group and 24 in the control group). The stimuli for the FER task were obtained from the Chinese Facial Affective Picture System (CFAPS). Four facial expressions (fearful, disgusted, sad, and angry) were used. The Pittsburgh Sleep Quality Index (PSQI), Self-Rating Anxiety Scale, and Self-Rating Depression Scale were used to measure participants’ sleep quality and psychological conditions. In Study 1, FER ability was compared between good and poor sleepers. In Study 2, all participants were sleep-deprived for one night, and completed the FER task before and after sleep deprivation. After different interventions (ie, napping for one hour, or walking around for ten minutes), the participants completed the third FER task.Results: Study 1: Poor sleepers were able to recognize sad expressions more accurately compared with good sleepers. Study 2: 30-h sleep deprivation had no significant effect on the accuracy (ACC). Napping after sleep deprivation improved the FER ACC of upper-face expressions and marginally significantly improved the FER ACC of disgusted expressions.Conclusion: Better sleep quality was linked to lower FER accuracy, particularly in recognizing sad expressions, while no significant differences in recognition speed were observed. Additionally, 30 hours of sleep deprivation did not affect FER accuracy, but napping after sleep deprivation improved accuracy for upper-face and marginally for disgusted expressions.Keywords: facial emotion recognition, sleep quality, facial features, facial emotion, sleep deprivation, sleep loss